Inoculantes microbianos produzidos a partir de composto de lixo sólido para biorremediação de solos contaminados com óleo diesel - Leal, Aline Jaime; Rodrigues, Edmo Montes; Leal, Patrícia Lopes; Júlio, Aline Daniela Lopes; Fernandes, Rita de Cássia Rocha; Borges, Arnaldo Chaer; Tótola, Marcos Rogério (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2019)
Microbial activity can be stimulated to remove soil hydrocarbons after the introduction of hydrocarbonoclastic microorganisms on the environment. We developed microbial inoculants produced from municipal solid waste compost (MSWC) for the bioremediation of diesel-contaminated soils. Diesel application occurred every 4 days for inoculant A and every 8 days for inoculant B. Respirometric analysis, total heterotrophic bacteria count, and evaluation of residual total petroleum hydrocarbons (TPH) were performed. The inoculants were evaluated immediately after production and after storage either at room temperature or under refrigeration. The degradation of TPH after 20 days was greatest at 30 g/kg. At this concentration, biodegradation of TPH ranged from 98.3 to 99.4%. After storage, efficiency of inoculant A reached TPH degradation rates of 96.5% (room temperature) and 98.1% (refrigeration). Inoculant B showed significant decrease of efficiency after storage, especially at room temperature. The addition of inoculants significantly increased the density of culturable bacteria in soil contaminated with diesel, even after storage. The use of MSWC at a dose of 30 g/kg was an effective strategy for the bioremediation of soils contaminated with diesel, allowing the elimination of more than 99% of the contaminants in 20 days.